2010
DOI: 10.1093/brain/awq314
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 targeted to the mitochondrial intermembrane space prevents motor neuropathy in the Sod1 knockout mouse

Abstract: Motor axon degeneration is a critical but poorly understood event leading to weakness and muscle atrophy in motor neuron diseases. Here, we investigated oxidative stress-mediated axonal degeneration in mice lacking the antioxidant enzyme, Cu,Zn superoxide dismutase (SOD1). We demonstrate a progressive motor axonopathy in these mice and show that Sod1(-/-) primary motor neurons extend short axons in vitro with reduced mitochondrial density. Sod1(-/-) neurons also show oxidation of mitochondrial--but not cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 72 publications
6
107
0
Order By: Relevance
“…These findings imply that the mitochondrial redox environment plays a central role in regulating skeletal muscle mitochondrial function. In support of this, the physiological and functional importance of maintaining redox homeostasis within the MIS was recently highlighted in a transgenic model that exclusively expressed SOD1 within the MIS (mitoSOD1,Sod1 −/− ) from SOD1 −/− mice 23. The transgenic approach used in the mitoSOD1,Sod1 −/− model prevented the morphological and biochemical defects associated with progressive motor axonopathy in skeletal muscle of the SOD1 −/− rodents,23 highlighting the importance of SOD1 redox regulatory enzyme expression in the MIS, and implicated oxidative damage initiated at mitochondrial sites in the pathogenesis of motor axon degeneration.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 89%
See 3 more Smart Citations
“…These findings imply that the mitochondrial redox environment plays a central role in regulating skeletal muscle mitochondrial function. In support of this, the physiological and functional importance of maintaining redox homeostasis within the MIS was recently highlighted in a transgenic model that exclusively expressed SOD1 within the MIS (mitoSOD1,Sod1 −/− ) from SOD1 −/− mice 23. The transgenic approach used in the mitoSOD1,Sod1 −/− model prevented the morphological and biochemical defects associated with progressive motor axonopathy in skeletal muscle of the SOD1 −/− rodents,23 highlighting the importance of SOD1 redox regulatory enzyme expression in the MIS, and implicated oxidative damage initiated at mitochondrial sites in the pathogenesis of motor axon degeneration.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 89%
“…The impact of altered redox homeostasis in loss of neuromuscular integrity and function with ageing has been investigated in several murine models, which have undergone genetic modifications of redox signalling/homeostasis components 19, 23, 25, 29, 30, 31, 32, 33, 34, 240, 241, 242. Transgenic murine models have provided insight into the importance of RONS regulatory systems in lifespan and neuromuscular ageing, and it has been reported that SOD2 −/− ,243 GRX3 −/− ,244 GPX4 −/− ,245 TRX1 −/− ,246 TRX2 −/− ,247 TR1 −/− 248 and TR2 −/− 249 murine models are embryonically lethal.…”
Section: Non‐enzymatic Key Antioxidants That Contribute To the Maintementioning
confidence: 99%
See 2 more Smart Citations
“…Preparation of Mitochondrial Subcompartments and Proteinase K Protection Assays-For protein localization, pure brain mitochondria were isolated using a Percoll gradient as described previously (29). 500 g of mitochondria (10 mg/ml) were resuspended in MS-EGTA (225 mM mannitol, 75 mM sucrose, 5 mM HEPES, 1 mM EGTA, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%